The adventures of Huckleberry Finn Level 3 - Twain, Mark; Votaw, John; Hopkins, Andy; Potter, Jocelyn (England Pearson Education Ltd, 2008)
This book is about Huck and Jim traveling along the Mississippi River from St. Petersburg to Cairo. Jim is a runaway slave so they have to be careful. They have a lot of adventures on the river. They even meet a king! But is he real? Huck soon finds out the truth.
Keywords: Tham khảo